Discontinuation of Cerebro-Spinal Fluid (CSF) Drainage in Acute Hydrocephalus: A Prospective Cohort Study and Exploratory Data Analysis - Anand S. Pandit; Joanna Palasz; Lauren Harris; Parashkev Nachev; Ahmed K. Toma (NeuroSci, 2024)
Background: The optimal management of CSF drainage in acute hydrocephalus, in particular when to initiate drain weaning, remains uncertain. This study aimed to evaluate the impact of timing and method of drain weaning on patient outcomes. Methods: This prospective observational study in a large-volume tertiary neuroscience centre included all adult patients who required temporary CSF drainage for acute hydrocephalus of any cause between January 2020 and March 2021. Contemporaneous data collection was conducted, including patient demographics, time to clamp, weaning methods, and clinical outcomes of hospital length of stay (LOS), rate of shunt insertion, drain-related infections, and mechanical complications. Univariate and multivariate statistical analyses were performed to identify the independent associations of timing-related factors. Results: A total of 69 patients were included (mean age = 59.4 years). A total of 59% had CSF diversion for aneurysmal subarachnoid haemorrhage, and 88% had EVD drainage. The length of drainage prior to the first clamp was significantly associated with the overall length of drainage (p < 0.0001), LOS (p = 0.004), and time to shunt (p = 0.02) following multivariate adjustment. For each day delayed in initiating the drain challenge, the overall LOS increased by an additional 1.25 days. There was no association between the weaning method and LOS, the rate of shunting, or CNS infection; however, those in the gradually weaned group had more mechanical complications, such as drain blockage or CSF leakage, than those rapidly weaned (p = 0.03) after adjustment. Discussion: This study recommends challenging the drain early via a rapid wean to reduce LOS, mechanical complications, and possibly infections. The consequences of temporary CSF diversion have significant implications at financial and patient levels, but the quality of evidence regarding weaning remains poor. Further randomised multicentre studies and national databases of practice are required to allow definitive conclusions to be drawn.